Evaluation of the Weekly Disease Surveillance System in Matabeleland South Province, Zimbabwe, 2018 - Tendai Chipendo; Rudo Chikodzore; Notion Tafara Gombe; Tsitsi Juru; Simbarashe Chiwanda; Mufuta Tshimanga (Journal of Interventional Epidemiology and Public Health)
Background: The weekly disease surveillance system (WDSS) acts as an early warning of potential threats to public health. In 2018, the reporting rates in Matabeleland South Province were below the 100% target, with overall timeliness of 61.7% and completeness of 67.3%. Low reporting rates may imply late detection of outbreaks in the province. The study was conducted to evaluate the WDSS in Matabeleland South province.